Effect of temperature to the properties of sago starch - Mustafa Kamal, M.; Rubiyah, Baini; Shahrol, Mohamaddan; Onni Suhaiza, Selaman; Nur Syuhada, Ahmad Zauzi; Md. Rezaur, Rahman; Abdul Rahman, N.; Chong, K.H; Atan, M. F.; Abdul Samat, N.A.S.; S.N.L., Taib; Othman, A.K. (IOP Publishing Ltd, 2017)
Recently, the importance of sago starch has increased, as it has become one of the main economically important agricultural crops to the most Southeast Asia countries. In the present work, an analysis on drying process of sago starch (Metroxylon sagu Rottb.) underwent various temperature has been made by using four empirical equations. The main goal of this analysis is to suggest the most accurate equation, in order to model and simulate the mechanical drying of sago starch. The experimental investigations were carried out in a gravity convection lab oven; and ±50g of sago starch (sample heights of 1 cm) was dried through four different temperatures, which were 50, 60, 70 and 80ºC. The effect of drying temperature on the drying kinetics, as well as various qualities attributes of sago starch, such as microstructure, colour and functional properties were investigated. The results suggested that drying temperature has significant effect on sago starch drying kinetic; therefore, drying temperature would be the basis to select drying condition. Meanwhile, it was found that the various drying temperature ranging from 50 to 80ºC affected the product quality especially in term of colour.